2010
DOI: 10.1111/j.1365-2141.2010.08478.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune reconstitution in children following chemotherapy for haematological malignancies: a long‐term follow‐up

Abstract: SummaryModern intensive chemotherapy for childhood haematological malignancies has led to high cure rates, but has detrimental effects on the immune system. There is little knowledge concerning long-term recovery of the adaptive immune system. Here we studied the long-term reconstitution of the adaptive immune system in 31 children treated for haematological malignancies between July 2000 and October 2006. We performed detailed phenotypical and functional analyses of the various B and T cell subpopulations unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 49 publications
1
58
1
2
Order By: Relevance
“…A preliminary case series study also indicates that PF has the potential to ameliorate several side effects caused by chemotherapy in humans (Safdie et al, 2009). One of the side effects, myelosuppression, is often dose-limiting in chemotherapy treatment, in part because damage to adult stem/progenitor cells impairs tissue repair and regeneration (Kofman et al, 2012; Mackall et al, 1994; van Tilburg et al, 2011; Williams et al, 2004). Despite the rising interest in nutrient-dependent changes in stem cell populations, little is known about how acute or periodic dietary interventions affect the hematopoietic system.…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary case series study also indicates that PF has the potential to ameliorate several side effects caused by chemotherapy in humans (Safdie et al, 2009). One of the side effects, myelosuppression, is often dose-limiting in chemotherapy treatment, in part because damage to adult stem/progenitor cells impairs tissue repair and regeneration (Kofman et al, 2012; Mackall et al, 1994; van Tilburg et al, 2011; Williams et al, 2004). Despite the rising interest in nutrient-dependent changes in stem cell populations, little is known about how acute or periodic dietary interventions affect the hematopoietic system.…”
Section: Introductionmentioning
confidence: 99%
“…There are reports of reduction in naïve T cells, while the memory compartment survives relatively well resulting in only mild defect in overall number of T cells. [1][2][3][4] The data on B-cell recovery are sparse. Previous studies have shown considerable B-cell decline both in bone marrow and peripheral blood followed by rapid recovery after cessation of chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Most authors agree that the interval time of 6–12 months is adequate to achieve a sufficient immune recovery that, in turn, has a key role in determining the response to vaccination [14, 20, 83, 8588, 91, 95, 96], but some studies have shown good results after reimmunization with inactivated vaccines already at 3 months [87]. …”
Section: Resultsmentioning
confidence: 99%